PENGARUH DESAIN PESAN KAMPANYE PROTOKOL KESEHATAN 3M OLEH KEMENTERIAN KOMINFO TERHADAP SIKAP MENJALANKAN PROTOKOL KESEHATAN 3M (Survei Pada Followers Instagram @kemenkominfo) - Shania Sekar Majid (2021)
During Covid-19, there were hundreds of campaign messages with various design content spread in public spaces or social media regarding the 3M Health Protocol. One of the campaign messages that were spread contained elements of ethos, pathos, and logos, namely a campaign that was disseminated by the Ministry of Communications and Informatics through Instagram social media. Starting from this uniqueness, researchers are interested in researching this campaign with the aim of proving whether there is a positive influence from the message design of the 3M health protocol campaign by the Ministry of Communications and Informatics on the attitude of implementing the 3M health protocol, especially Instagram followers @kemenkominfo. The theory used in this research is Aristotle's Theory of Rhetoric. The approach in this study uses a quantitative approach with a survey method. This research was conducted for 10 months from October to July. The sample in this study found 100 respondents using purposive sampling technique. The test instrument uses validity and reliability tests. Data analysis in this study used correlation test, simple linear regression test, T test, and analysis of variance test. The results of this study indicate that H0 is rejected and H1 is accepted, which means that there is a positive influence from the design of the 3M health protocol campaign message by the Ministry of Communications and Informatics on people's attitudes in implementing the 3M health protocol.